Intersectional sustainability and student activism: A framework for achieving social sustainability on university campuses. (March 2021) - Hudler, Keara; Dennis, Lilly; DiNella, Muriel; Ford, Nataley; Mendez, Joanna; Long, Joshua
In recent decades, universities have made significant progress toward environmental sustainability and have likewise tightened their budgets and restructured economic models in the name of financial sustainability. However, institutions of higher education have failed to address issues of social sustainability and social injustice, many of which are increasing in number and severity on college campuses. This article takes a student activist perspective on these issues, suggesting that a comprehensive and intersectional approach toward university sustainability (with particular re -affirmation of the social sustainability pillar) can empower students and their allies, raise awareness about the causes of these issues, and allow a more constructive environment for collaborative approaches and policy formation on college campuses.